2013
DOI: 10.1111/nph.12176
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose functions as a signal involved in the regulation of strawberry fruit development and ripening

Abstract: Summary Fleshy fruits are classically divided into climacteric and nonclimacteric types. It has long been thought that the ripening of climacteric and nonclimacteric fruits is regulated by ethylene and abscisic acid (ABA), respectively. Here, we report that sucrose functions as a signal in the ripening of strawberry (Fragaria × ananassa), a nonclimacteric fruit. Pharmacological experiments, as well as gain‐ and loss‐of‐function studies, were performed to demonstrate the critical role of sucrose in the regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
217
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 255 publications
(227 citation statements)
references
References 63 publications
9
217
0
1
Order By: Relevance
“…However, recently, several studies showed that Suc also functions as a signaling molecule involved in regulation of various physiological processes in plants such as root growth, fruit development and ripening, and hypocotyl elongation (Kircher and Schopfer, 2012;Lilley et al, 2012;Jia et al, 2013;Ruan, 2014). In this study, we found that Fe deficiency-induced root FCR activity and expression of FRO2 and IRT1 were significantly further up-regulated by exogenous Suc ( Fig.…”
Section: Discussionsupporting
confidence: 60%
“…However, recently, several studies showed that Suc also functions as a signaling molecule involved in regulation of various physiological processes in plants such as root growth, fruit development and ripening, and hypocotyl elongation (Kircher and Schopfer, 2012;Lilley et al, 2012;Jia et al, 2013;Ruan, 2014). In this study, we found that Fe deficiency-induced root FCR activity and expression of FRO2 and IRT1 were significantly further up-regulated by exogenous Suc ( Fig.…”
Section: Discussionsupporting
confidence: 60%
“…2) suggests that FaSnRK2.6 is an important regulator of strawberry fruit development and ripening. To test this possibility, we performed loss-and gain-of-function experiments using transient overexpression (OE) and RNA interference (RNAi) techniques (Jia et al, 2013b). As shown in Figure 4A, FaSnRK2.6-OE resulted in a more than 4-fold increase in the level of FaSnRK2.6 transcript, whereas FaSnRK2.6-RNAi resulted in a dramatic decrease in FaSnRK2.6 transcript level.…”
Section: Manipulation Of Fasnrk26 Expression Modulated Fruit Developmentioning
confidence: 99%
“…Expression of FaSnRK2.6 in Response to Internal Signals As ABA and Suc have been identified as internal signals that control strawberry fruit development and ripening (Jia et al, , 2013b, we examined the expression of FaSnRK2.6 in response to ABA and Suc stimuli in fruits. As shown in Figure 3A, the level of FaSnRK2.6 expression declined upon ABA treatment in a concentrationdependent manner.…”
Section: Genome-wide Identification Of Fasnrk2 Subfamily Membersmentioning
confidence: 99%
See 2 more Smart Citations